Importance of Forensic Audit with respect to Income Tax Evasion (ISR) in Panama - Galindo-Alabarca, Mayuri Cecibell; Yepes-Jiménez, Isabel Cristina; Acosta-Quintero, Dayana Marcela; Casanueva-Yáñez, Galvarino (Journal of Posthumanism, 2025)
In all countries, the Tax Administration (TA) in Panama faces challenges intrinsic to problems related to tax evasion. The objective of this article is to analyze the relationship between the independent variables Forensic Audit and Income Tax (ISR). This research is characterized by a mixed approach, with a descriptive, correlative and explanatory approach. First, a Likert-type questionnaire with a dichotomous configuration was developed. The quantitative analysis makes a comparison between the income of the ISR and those of the CI, IT and the national collection agency. The findings show deficiencies in the management of theoretical models of FA, with little participation in judicial processes reviewed by expert reports and other fiscal evaluations. It is essential to take into account, and most importantly, the ability to have an AF model that incorporates specialized elements of the FA in order to detect evasive actions of the ISR.